Analysis of non-Newtonian magnetic Casson blood flow in an inclined stenosed artery using Caputo-Fabrizio fractional derivatives. (May 2021) - Jamil, Dzuliana Fatin; Saleem, S.; Roslan, Rozaini; Al-Mubaddel, Fahad S.; Rahimi-Gorji, Mohammad; Issakhov, Alibek; Din, Salah Ud
Highlight: The blood is modelled as non-Newtonian Casson fluid. The velocities of blood and magnetic particles are highly influenced by the fractional order parameter. In general, the particle velocity is lower than the blood velocity. The blood and particle velocities increase with respect to Reynold number and Casson fluid parameters. The blood velocity decreases with respect to Hartmann number. Abstract: Background and Objective: Arterial diseases would lead to several serious disorders in the cardiovascular system such as atherosclerosis. These disorders are mainly caused by the presence of fatty deposits, cholesterol and lipoproteins inside blood vessel. This paper deals with the analysis of non-Newtonian magnetic blood flow in an inclined stenosed artery. Methods: The Casson fluid was used to model the blood that flows under the influences of uniformly distributed magnetic field and oscillating pressure gradient. The governing fractional differential equations were expressed using the Caputo Fabrizio fractional derivative without singular kernel. Results: The analytical solutions of velocities for non-Newtonian model were then calculated by means of Laplace and finite Hankel transforms. These velocities were then presented graphically. The result shows that the velocity increases with respect to Reynolds number and Casson parameter, while decreases when Hartmann number increases. Conclusions: Casson blood was treated as the non-Newtonian fluid. The MHD blood flow was accelerated by pressure gradient. These findings are beneficial for studying atherosclerosis therapy, the diagnosis and therapeutic treatment of some medical problems.